2020
DOI: 10.1103/physreva.102.023313
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and static response of anomalous one-dimensional fermions via a quantum Monte Carlo approach in the worldline representation

Abstract: A system of three-species fermions in one spatial dimension (1D) with a contact three-body interaction is known to display a scale anomaly. This anomaly is identical to that of a two-dimensional (2D) system of twospecies fermions. The exact relation between those two systems, however, is limited to the two-particle sector of the 2D case and the three-particle sector of the 1D case. Here, we implement a nonperturbative Monte Carlo approach, based on the worldline representation, to calculate the thermodynamics … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 51 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…Also, we do not consider the three-body interaction whose effect has already been investigated in Refs. [63,64,66,67]. While the three-body attraction tends to stabilize three-body bound states, here we are interested in the stabilization of them due to the purely two-body attractions.…”
Section: Hamiltonianmentioning
confidence: 99%
“…Also, we do not consider the three-body interaction whose effect has already been investigated in Refs. [63,64,66,67]. While the three-body attraction tends to stabilize three-body bound states, here we are interested in the stabilization of them due to the purely two-body attractions.…”
Section: Hamiltonianmentioning
confidence: 99%
“…The Cooper triple state does not necessarily form a condensate (however, note Ref. [45]), but resulting three-body correlations can modify the equation of state substantially [40,46]. In this paper, motivated by the recent astronomical observations of compact stars as well as the theoretical progress in the in-medium three-body correlations in cold atomic systems, we discuss the possible scenario of the density-induced hadron-quark crossover accompanied by the formation of Cooper triples using a simplified toy model with threequark attractive interaction responsible for the baryon formation.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of the SU (3) fermions with attractive threebody contact interaction was extensively discussed in the articles of Drut et al [2][3][4]. It was shown that this system features a scale anomaly, which impacts the thermodynamics [5] and exact universal relations generalizing the Tan contact theorems for three-body forces. The quantum anomaly also affects [6] the high-temperature transport properties of the three-component Fermi gases.…”
Section: Introductionmentioning
confidence: 99%